Stiffness properties of porous silicon nanowires fabricated by electrochemical and laser-induced etching - K., Omar; Y., Al-Douri; A., Ramizy; Z., Hassan (Elsevier Ltd., 2011)
Link to publisher's homepage at http://www.elsevier.com/wps/find/homepage.cws_home